Comparison of Extrapleural Anterolateral Decompression and Transthoracic Anterior Decompression for Tuberculosis of The Dorsal Spine - Karn, Navin Kumar; Jha, Ranjeev; Sitoula, Prakash; Singh, Mahipal; Jain, Anil Kumar (Journal of Nobel Medical College, 2015)
Background: Spinal tuberculosis (TB) comprises 50% of all skeletal tuberculosis and it affects body of the vertebra in about 98% of the cases, hence surgical decompression when needed should be anterior. There are a number of studies describing transthoracic approach but very few describing extrapleural anterolateral approach and none were comparative trial. Therefore, the present study was conducted to compare extrapleural anterolateral decompression and transthoracic anterior decompression for tuberculosis of dorsal spine. Aims and Objectives: To compare the duration of surgery, amount of blood loss, neurological recovery and complication rate. Design: Prospective Randomised controlled Trial Setting: The study was performed in Department of Orthopedics, NMCH,Biratnagar, Nepal Material and methods: The patients with tuberculosis of dorsal spine those required surgical decompression were randomly allocated into two groups. For the first group we performed extrapleural anterolateral decompression and for the second group we performed transthoracic anterior decompression We excluded patients with ischemic heart disease, end stage renal disease, immunocom promised stage. We did follow up for one year with comparing outcome in terms of duration of surgery, amount of blood loss neurological recovery and complication rate. Results: 60 patients were left after exclusion. We found duration of surgery, amount of blood loss were significantly higher in transthoracic anterior decompression group. There was single case of wound infection (3.3%)in the transthoracic anterior decompression group. 3 cases of transthoracic anterior decompression had to convert into anterolateral decompression because of adhesion of pleura to lung. There was no significant difference in neurological recovery and development of kyphotic deformity. Conclusion: We found anterolateral decompression did better than transthoracic anterior decompression in terms of duration of surgery, amount of blood loss, postoperative morbidity but similar neurological recovery rate. DOI: http://dx.doi.org/10.3126/jonmc.v3i1.12237 Journal of Nobel Medical College Vol. 3, No.1 Issue 6, 2014, Page: 46-51